Understanding the Unfolded Protein Response in the Pathogenesis of Asthma - Pathinayake, Prabuddha S.; Hsu, Alan C.-Y.; Waters, David W.; Hansbro, Philip M.; Wood, Lisa G.; Wark, Peter A. B. (Frontiers in Immunology, 2018)
Abstract Asthma is a heterogeneous, chronic inflammatory disease of the airways. It’s a complex disease with different clinical phenotypes and results in a substantial socio-economic burden globally. Poor understanding of pathogenic mechanisms of the disease hinders the investigation into novel therapeutics. Emerging evidence of the unfolded protein response (UPR) in the endoplasmic reticulum (ER) has demonstrated previously unknown functions of this response in asthma development. A worsening of asthmatic condition can be brought on by stimuli such as oxidative stress, pathogenic infections, and allergen exposure. All of which can induce ER stress and activate UPR leading to activation of different inflammatory responses, and dysregulates the innate immune functions in the airways. The UPR as a central regulator of asthma pathogenesis may explains several unknown mechanism of the disease onset which lead us in new directions for future asthma treatments. In this review we summarize and discuss the causes and impact of ER-UPR in driving the pathogenesis of asthma and highlight its importance in clinical implications.